Pemberdayaan UMKM melalui Digitalisasi dan E-Commerce - Romadhon, M Nurul; Aisah, Eviana Nur; Maulidina, Ahmad Rizal; Mufid, Abdul (Kifah: Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to develop the promotion and sales of MSMEs in Pringgoboyo village, Maduran sub-district, Lapmongan Regency. This village has various UMKM potentials but has only reached local marketing, namely traditional markets. In the modern era, digital marketing is growing rapidly with various applications that can reach consumers in various regions and many people from teenagers to adults have smartphones, but the use of these smartphones is not optimal, especially for MSME owners. Therefore, the people of Pringgoboyo village can develop the potential of MSMEs with a wider reach in utilizing digital marketing through smartphones. Data collection is carried out using interview techniques to obtain information, the data that has been obtained is then analyzed and described in accordance with the KKN-PAR stage. Due to the rapid development of digital, we have created a digital marketing training that can help the people of Pringgoboyo village. The community realizes the importance of digital marketing as a utilization of MSME product marketing.